Clinic and hematological indices of broiler-chickens under organic growing - Кучерук, М. Д.; Засєкін, Д. А. (Scientific Progress & Innovations, 2018)
The article is devoted to the study of the possibility of growing broiler-chickens in an organic way to produce high-quality and safe chicken. The growing process, the dynamics of a set of live weight of organic growing chickens are compared with the traditional intensive technology. Organic foods are healthier for consumers than traditional ones. The productivity, well-being and health of farm animals depend not only on feeding, but also on the conditions of maintenance and care. The hematological research promotes the study of the influence of a certain factor on the mechanisms of regulation of metabolic homeostasis of the internal environment of the organism and the productivity of the poultry. The issues of changes in the biochemical and morphological parameters of peripheral blood over time are highlighted. Studies have not revealed pathological abnormalities in the blood picture of chickens of different ages. Some fluctuations in blood glucose, as well as protein and hemoglobin, respectively, in most control points corresponded to age periods of growth and development, but also some influence of environmental stress factors (elevated air temperature) was noted. The dynamics of oscillations of blood cells was within the physiological norm for chickens of slowly growing breeds. Significant deviations testifying the violation of the health status of the poultry were not established. The humane component of organic chicken raising covers the economic costs associated with a longer period of keeping and organic products have added value. However, only with the creation of proper conditions for the maintenance and care of poultry to meet their natural needs, when feeding with natural, environmentally friendly feed – you can ultimately receive high-quality and safe organic products.